Ab Initio Prediction of Stable Crystal Structure of Procarbazine Molecule (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
The crystal structure of procarbazine molecule was predicted using first principles of quantum mechanics. The gas phase optimization was carried out by density functional theory and the resulted geometric coordinates were utilized for the search of hypothetical packings which reveals the possible stable conformers under a repulsion alone potential field with minimum cell volume. The thermodynamically favor structure was resulted from the lattice energy minimization of these hypothetical structures from the using the repulsion-dispersion potential field. The stability of global minimum structure was confirmed from the hydrogen bond interactions and second derivative properties.
Keywords: Lowest energy conformer; X-ray diffraction; Fingerprint plot; Mechanical stiffness